Post-Traumatic Hypopituitarism—Who Should Be Screened, When, and How? - Quinn, Mark; Agha, Amar (Frontiers in Endocrinology, 2018)
Traumatic brain injury (TBI) remains a major, global public health concern. Over the last 15 years, a significant body of evidence has emerged demonstrating that post-traumatic hypopituitarism (PTHP) is a common and clinically significant consequence of TBI. Non-specific symptomology and the lack of an agreed approach to screening for PTHP has led to significant under-diagnosis of this debilitating disease. In this review, we will discuss the frequency and clinical significance of acute and chronic PTHP as described in the current literature highlighting the evidence base for screening and hormone replacement in these patients. We will also offer a pragmatic approach to identifying relevant anterior pituitary dysfunction after TBI and a follow-up strategy for those patients. Specific controversies and remaining unanswered questions will be addressed.